PROFIL KEBAHAGIAAN SISWA BERPRESTASI DI MADRASAH TSANAWIYAH NEGERI (MTSN) - Ikhwanul Hasan; Nurfarhanah; Yarmis Syukur; Frischa Meivilona Yendi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Happiness is a crucial aspect of student psychological development, particularly for high-achieving students who often experience increased pressure in academic activities. This study aims to describe the happiness profile of high-achieving students at a State Islamic Junior High School (MTsN). The research approach used was descriptive qualitative, with data collection techniques including in-depth interviews, observation, and documentation. This study also employed data triangulation, as the data were gathered from diverse, mutually reinforcing sources: the guidance counselor, parents, the principal, peers, and the homeroom teacher. The subjects were three high-achieving students selected based on academic and non-academic achievement criteria. The results indicate that high- achieving students at MTsN generally have high levels of happiness, influenced by social support from family, teachers, peers, and personal achievements recognized by the school environment. This study recommends a holistic approach to supporting high-achieving students to maintain emotional, social, academic, and non-academic balance.